(untitled) (KYAMC Journal, 2021)
Background: Older people are especially vulnerable to emergencies. Those with progressive loss of function in particular can have difficulty in adapting to challenges and coping with disruptions. Objective: To assess experience and suggestions regarding disaster preparedness among the older people in a rural community of Bangladesh. Materials and Methods: This cross-sectional descriptive study was conducted in Shahzadpur upazila of Sirajganj district from 1st July 2015 to 30th September 2015. Purposive sampling technique was adopted. Total 485 households were surveyed. One elderly in a household was interviewed to get relevant information. Collected data were cleaned and entered in computer for analyses. Results: Age of the respondents ranged from 60 to 79 years. Majority (53.4%) was female; 38.1% were housewives, 57.9% were illiterates, 54% lived in tin-shed houses and 73% had sanitary latrines. Regarding social status 88% got adequate food, 80% got necessary clothing, 33% got pocket money and 79% got support during illness. Most frequently observed disaster was flood. They managed their shelter by bed elevation, moving to higher places, staying on boat etc. They suggested that disaster preparedness should include dry food preservation, safe drinking water support, medical support, public shelter, making of dam in frequently affected area and support from government. Conclusion: With demographic changes growing number of disasters create problems for elderly. To solve these special problems, ageing issues should be taken into consideration. KYAMC Journal Vol. 11, No.-4, January 2021, Page 176-180